Pengembangan Bahan Ajar Geometri Berbasis Kearifan Lokal Aceh - Fitriani Fitriani; Wahidah Wahidah; Junaidi Junaidi (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2021)
The results of observations on April 15, 2019, at SMP Negeri 1 Peureulak, East Aceh District, and the 2017/2018 National Examinations showed that students experienced difficulties in geometry, so there was a need for teaching materials in the form of LAS (Student Activity Sheets). This development aims to determine that teaching materials in the form of LAS based on Acehnese local wisdom are valid, practical, and effective, and also determine student learning outcomes. This research is a development research using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The subject of the trial in this study was grade VII-1 students of SMP Negeri 1 Peureulak, East Aceh District. Questionnaires, observations, interviews, and tests are used as data collection techniques and instruments in this research. The data analysis in this study is descriptive analysis using the preparation/development of the LAS product variable and the resulting LAS quality variable. As for student learning outcomes in using LAS can be seen from the results of the LAS analysis, which includes student learning outcomes as one of the effectiveness aspect of LAS and test data on learning outcomes. Based on the results of the analysis, it can be concluded that the teaching materials in the form of LAS based on Acehnese local wisdom in mathematics learning especially geometry material in Junior High Schools are categorized as valid, practical, and effective. Student learning outcomes using the LAS have a mastery score with a score of 86.43.